The new smart approach to bath design - Maney, Susan (New Jersey Creative Homeowner, 2003)
"Revised and updated, The New Smart Approach to Bath Design has all the answers and inspiration for anyone who is contemplating adding or remodeling a powder room, a family bath, or even an at-home spa in a master retreat. With more than 260 gorgeous color photographs, this best-selling book offers the finest examples of bath design today and includes updates on the latest trends, products, and technology." - Provided by publisher
Includes index.
FA-2533g donated by D. Gonzales.
Keywords: Bathrooms -- Remodeling